Zoneamento geoambiental da Quarta Colônia Rio Grande do Sul - Schirmer, Gerson Jonas (2015)
This paper presents a proposal for Geoenvironmental Zoning for Quarta Colônia, comprising the municipalities of: Agudo, Dona Francisca, Faxinal do Soturno, Ivora, Palma Nova, Pinhal Grande, Restinga Seca, Silveira Martins, São João do Polêsine, located in the Central region Rio Grande do Sul. In this thesis, there was focus on the detail of the elements that make up the landscape, carrying information from crosses between land use with the other elements that make up the landscape, to determine existing environmental conflicts in the study area and facilitate the development of Geoenvironmental Zoning. Justified the search by the existing demand for a job of this magnitude in the study area. The geo-environmental systems represent the integration of characteristics of the physical elements of the study area, in the face of social activities, developed by the occupation who developed and transformed the local landscape. The methodology is based on a systemic approach to landscape using GIS as a tool (Geographical Information Systems). Through a representative synthesis, five systems were defined, which characterized the geoenvironmental landscape of the municipalities studied. The Urban System consists of the headquarters of the municipalities studied. The slopes System Plateau rim, where there is greater concentration of woody vegetation and susceptibility of occurrence of mass movement processes. In rice paddies System ramps Recent Deposits human action results in environmental conflicts, especially regarding the occupation in areas of Permanent Preservation Areas. Furthermore, there is likely to become risk areas flood periods. The Hills Low Altitude System consists of two differentiation with regard to occupation and geomorphological processes, which are: Hills in Sedimentary Rocks the Hill, with significant anthropogenic occupation and Hills and Sedimentary Rocks Low Altitude. The Volcanic Hills High Altitudes system composed of: Altitudes Hills in Crispy Rocks, Volcanic Hills with Medium Properties and Volcanic Hills with Small Properties. In this sense, this thesis provides a theoretical framework for the study and verification of the potential and environmental restrictions, allowing maximization of proposals for sustainable development to communities as well as to serve as a base for conducting further studies in these municipalities. It was concluded that this Geoenvironmental Zoning allowed to determine the main areas of existing environmental conflict between land use with the natural elements of the landscape.